Melatonin promotes reduction in TNF levels and improves the lipid profile and insulin sensitivity in pinealectomized rats with periodontal disease - Santos, Rodrigo Martins dos [UNESP]; Marani, Fernando [UNESP]; Chiba, Fernando Yamamoto [UNESP]; Mattera, Maria Sara de Lima Coutinho [UNESP]; Tsosura, Thais Verônica Saori [UNESP]; Tessarin, Gestter Willian Lattari [UNESP]; Pereira, Renato Felipe [UNESP]; Belardi, Bianca Elvira [UNESP]; Pinheiro, Beatriz Costa E Silva [UNESP]; Sumida, Doris Hissako [UNESP] (Elsevier, 2018)
Aim: This study aimed to investigate the effects of melatonin (ME) on insulin resistance (IR) and signaling (IS), proinflammatory cytokine levels, and lipid profiles in pinealectomyzed (PNX) rats with periodontal disease (PD). Main methods: One hundred and forty-four rats (age = 40 days) were distributed into 8 groups: 1) control (CN); 2) PD only; 3) PNX only; 4) PNX and PD (PNXPD); 5) CN treated with ME (CNM); 6) PD treated with ME (PDM); 7) PNX treated with ME(PNXM); 8) PNX and PD treated with ME(PNXPDM). The PNX groups were subjected to pinealectomy at 40 and at 60 days of age. The animals were then subjected to PD induction in the mandibular first molars. After PD induction, the ME replacement therapy (MERT-5 mg/kg body weight) was performed using water for 28 days. After this period, the plasma concentration of glucose, insulin, TNF, IL-6, triglycerides, total cholesterol, HDL-cholesterol, LDL-cholesterol, and VLDL-cholesterol and the HOMA-IR index were determined. Akt serine phosphorylation status in the white adipose tissue, gastrocnemius muscle, and rat liver were also evaluated. Key findings: PD, PNX, and PNXPD groups showed an increase in IR with elevated plasma levels of insulin and TNF compared to CN group. PNX and PNXPD groups presented alteration in lipid profile compared to CN group. MERT improved all of the analyzed parameters. No difference was observed in the IS among different groups. Significance: The results suggest that MERT efficiently prevents IR, improves lipid profile, and increases plasma levels of insulin and TNF in PD and PNX rats.
Keywords: Cholesterol; Insulin resistance; Melatonin; Periodontal diseases; Pineal gland